The formation of superhard coatings = 48 GPa in Ti-Hf-N (Fe) and analysis of their structure and properties. - Pogrebnjak, A. D.; Ponomarev, A. G.; Kaverin, M. V.; Kolesnikov, D. A.; Beresnev, V. M.; Komarov, F.F.; Mel’nik, S. S. (International Conference on Plasma Surface Engineering, 2013)
Superhard nanostructured Ti–Hf–N(Fe) coatings are prepared. The formation of local regions of (Ti, Hf)N, FeN, and Hf is detected using µ-PIXE (ion microbeam). It is revealed that the synthesized coatings have a nanohardness of 48 ± 1 GPa and are composed of nanograins with a size of 4.8–10.6 nm, which are enveloped by finer entities of other phases (Ti, Fe)N and FeN. There is a good correlation between the results derived by XRD, TEM, AFM, and SEM and microanalysis, which in turn are complemented by the analysis results obtained using an ion microbeam and PIXE.